A Progression to Transfer RIRD to the Natural Environment. (16th March 2016) - Martinez, Catherine K.; Betz, Alison M.; Liddon, Clare J.; Werle, Rebecca L.
Abstract : Response interruption and redirection has been shown to be effective for decreasing vocal stereotypy, but treatment effects in the natural environment have yet to be documented in the literature. A recent review indicated the paucity of studies that implemented response interruption and redirection during typically occurring activities or for sessions longer than 5–10 min. One method to promote generalization across settings may be stimulus control procedures. The purpose of the current study was to evaluate the progression of the intervention from a highly structured to a more natural setting, and across longer durations. We also investigated the extent to which a signal could acquire stimulus control over stereotypy. Although we were unable to bring stereotypy under the inhibitory control of a signal alone, we maintained low levels of stereotypy in the natural environment and ultimately extended sessions up to 30 min. Clinical implications and areas for future research are discussed. Copyright © 2016 John Wiley & Sons, Ltd.